STRATEGI PENGEMBANGAN USAHA KECIL MENENGAH (UKM) PENGOLAHAN IKAN ASAP YANG BERORIENTASI PASAR DI KABUPATEN BONE - Rafi Ohorella; Mulyono S. Baskoro; Sri Harijati (LPPM Universitas Terbuka, 2022)
This study aims to examine the conditions of, and formulate a strategy for, developing smoked fish processing in small and medium enterprises (SMEs) in Bone Regency. Methods of data collection include interviews, field observations, and documentation with questionnaires. Method of data analysis include descriptive analysis of the conditions and characteristics of smoked fish processing SMEs, SWOT (Strength-Weakness-Opportunities-Threat) analysis and QSPM (Quantitative Strategic Planning Matrix) methods to formulate priority strategies for developing smoked fish processing SMEs. The results show the following conditions of smoked fish processing in Bone Regency: 100% of the SMEs use simple technologies, 79% have low education, 91.94% of the workforce was of productive age. The SMEs development strategies that can be learned include strategies for establishing cooperative relationships and government support in promoting smoked fish processed products, strategies for developing smoked fish processing SMEs with training and counseling programs from relevant agencies, strategies for implementing the latest processing technological innovations by renewing infrastructures of facilities, as well as strategies for completing business permits and legalities.Penelitian ini bertujuan untuk mengkaji kondisi dan merumuskan strategi pengembangan Usaha Kecil dan Menengah (UKM) pengolahan ikan asap di Kabupaten Bone. Pengumpulan data dilakukan dengan wawancara, observasi lapangan, dan dokumentasi dengan kuesioner sebagai alat bantu. Analisis dilakukan secara deskriptif terhadap kondisi dan karakteristik UKM pengolah ikan asap. Analisis iSWOT dan metode QSPM untuk merumuskan prioritas strategi pengembangan UKM pengolahan ikan asap. Hasil penelitian menunjukan bahwa kondisi pengolah ikan asap di Kabupaten Bone 100% menggunakan teknologi sederhana, 79% memiliki pendidikan rendah, serta umur tenaga kerja produktif sebanyak 91,94% dan strategi pengembangan UKM yang dapat di ambil adalah strategi menjalin hubungan kerjasama dan dukungan pemerintah dalam mempromosikan produk olahan ikan asap, strategi peningkatan/pengembangan UKM pengolahan ikan asap dengan program pelatihan dan penyuluhan dari dinas terkait, strategi penerapan inovasi-inovasi teknologi pengolahan terkini dengan pembaharuan sarana prasarana, serta strategi penyelesaian perizinan dan legalitas usaha.